Diversification of the Angolan exports : challenges and benefits - Paulo, Francisco Miguel (2014)
In recent years several researchers have published papers on exports concentration (diversification) urging policymakers in the undeveloped world to endeavour to diversify their exports since this can contribute to boost the growth of per capita GDP. Researchers such as Imbs and Wacziarg (2003) and Hesse (2008) found a non-linear U shaped curve relationship between export concentration and GDP per capita growth in several non-oil producing countries around the world. In order to investigate this relationship, for the case of Angola, a growth regression model was applied using OLS estimator with time series data from 1995 to 2011. This master dissertation investigates the case of Angola, an oil-producing country with one of highest export concentrations in the world, and found that the higher export concentration has been detrimental to the growth of GDP per capita taking into account that this growth would have been higher if the export concentration was lower ( higher diversification). Therefore, this master dissertation found a non-linear concave relationship between export concentration and GDP per capita growth in the case of oil-exporting countries1 and not a U shaped curve as other researches had found earlier (Imbs and Wackiazrg (2003) and Hesse (2008)). However running regression for some no-oil exporting countries2 we found in the U shaped curve, a case to say that the pattern followed by oil-exporting countries is different from the non-oil producing countries, perhaps due to the fact that oil-exporting countries have on average higher export concentration levels than the non-oil exporting countries.